1995
DOI: 10.1159/000246470
|View full text |Cite
|
Sign up to set email alerts
|

May <i>Helicohacter pylori</i> Be Important for Dermatologists

Abstract: Helicohacter pylori, a microaerophilic gram-negative bacterium, is the major cause of gastritis, plays a key role in the etiology of peptic ulcer and is a risk factor for gastric cancer. Although 50% of the population is affected, dermatologists seem to be unaware of the impact H. pylori may have on cutaneous pathology. Among skin diseases, H. pylori has been related so far only with chronic urticaria and rosacea. In rosacea, histology of the stomach mucosa revealed that 84% of 31 patients were H. pylori posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1
11

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 6 publications
1
55
1
11
Order By: Relevance
“…One possible explanation might be that the immunologic stimulation induced by infection might, through mediator release, causes a non-specific increase of the skin vessel sensitivity to agents increasing vascular permeability. 12 A number of agents might act through this mechanism. As a matter of fact, increased production of interleukin 8 (IL-8), platelet-activating factor (PAF) and leukotrienes (LT) B4 and C4 has been observed in the gastric mucosa of H. Pylori infected patients and these mediators exert evident actions on the skin.…”
Section: Methodsmentioning
confidence: 99%
“…One possible explanation might be that the immunologic stimulation induced by infection might, through mediator release, causes a non-specific increase of the skin vessel sensitivity to agents increasing vascular permeability. 12 A number of agents might act through this mechanism. As a matter of fact, increased production of interleukin 8 (IL-8), platelet-activating factor (PAF) and leukotrienes (LT) B4 and C4 has been observed in the gastric mucosa of H. Pylori infected patients and these mediators exert evident actions on the skin.…”
Section: Methodsmentioning
confidence: 99%
“…During these last few years, several studies have suggested a potential relationship between H. pylori and rosacea, as it has been shown that the prevalence of H. pylori infection is higher in patients affected by this condiction when compared to the general population (15). Moreover, it has been described that rosacea symptoms may improve after H. pylori eradication (16).…”
Section: Introductionmentioning
confidence: 99%
“…Acredita-se que mais de um terço dos carcinomas gástri-cos seja atribuído à infecção pelo H. pylori. 26,33,73,100 Outras afecções associadas à infecção pelo H. pylori são linfoma de tecido linfóide associado à mucosa gástrica -MALToma, 105 dispepsia não-ulcerativa, 10,12 doenças coronarianas e cardiovasculares, 90,108,98,107 urticária idiopática crônica, 29,110,129 doenças auto-imunes (púrpura de Henoch-Shönlein, 77,111 trombocitopenia auto-imune, 43 síndrome de Sjögren 37 ) e enxaqueca. 42 Estudos sugerem que existe aumento na incidên-cia de refluxo gastroesofágico (RGE) após erradicação do H. pylori da mucosa gástrica.…”
Section: Introductionunclassified